A global analysis of third generation mobile telecommunications market entry - Madden, Gary; Morey, Aaron; Bohlin, E. (International Telecommunications Society, 2011)
National regulatory authorities (NRAs) attempt to encourage participation in spectrum assignments by enhancing entrants’ likelihood of success. The question this study addresses is: Can NRA policy tools really affect the probability an entrant wins a 3G spectrum licence? In particular, the econometric analysis allows consideration of whether licence concession or mode of assignment encourages entry. The study finds that auction assignment processes only slightly increase the probability of entry, whilst price and quantity concessions have no impact.